Cowpeas for Kansas - Hildreth, W. R. (My University, 1902)
Introduction: The great need of Kansas is more leguminous crops as cowpeas, soy beans, clover and alfalfa. The superior value of these crops lies principally in their ‘nitrogen gathering’ power. On their roots are found tubercles. These are caused by bacteria which possess the power to gather free nitrogen from the air and prepare it for the use of the plant. In this way great stores of the most valuable as well as the most deficient of plant foods are obtained. The tubercles on the roots of cowpeas are larger than on the roots of any other legume, besides they form in Kansas soils without inoculation which is not the case with the soy bean. Another value of legumes is their high protein content. This constituent is very deficient in most Kansas feeds, as corn, prairie hay and the like, so in order to supply the need the feeder must buy high priced nitrogenous foods or raise leguminous crops. The cowpea is equal to alfalfa in protein content. The power of legumes to enrich the soil by adding nitrogen also adds to their value. Even when the hay crop is removed about one half of the nitrogen content of the plant remains in the roots and wasted leaves. The cow pea is superior to the soy bean as a fertilizer, and has the advantage of clover and alfalfa in being produced in one year or as a second crop. Since legumes have an extensive and deep root system they act as nature’s subsoiler. This deep root system enables the plant to bring plant food to the surface from a great depth, to loosen and aerate the soil and to withstand drought.
Citation: Hildreth, W. R. Cowpeas for Kansas. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Legumes; Nitrogen Fixing Bacteria; Kansas; Cow Pea; Agriculture; Theses